Novice Teachers’ Beliefs and Knowledge about Education for Sustainable Development - Zhukova, Olena; Fjodorova, Ilona; Iliško, Dzintra (Acta Paedagogica Vilnensia, 2020)
Incorporating education for sustainable development (ESD) into the curriculum is one of the main priorities of education policy in Latvia and internationally. Implementation of ESD relies greatly on individual teachers’ beliefs, enthusiasm, theoretical knowledge and practical expertise. It is widely recognized that teachers’ beliefs influence their decisions about the curriculum, pedagogy and assessment. While teachers’ beliefs and general pedagogical knowledge receive considerable attention in teacher education research worldwide, novice teachers’ beliefs and knowledge regarding sustainability and ESD are not widely discussed despite the widespread assumption that teacher’s preparedness and intention to teach ESD tend to be motivated by the beliefs and knowledge a teacher holds. Some education researchers argue that novice teachers tend to have limited understanding of sustainability and ESD. The aim of the research described in this article was to reveal the range of ways in which a sample of 32 volunteer novice teachers in Latvia perceive, understand and experience ESD, as well as how ESD relates to their professional practice. A phenomenographic approach is applied in this study. Data collection methods include semi-structured interviews, written questionnaires, and focus group discussions. The study revealed a range of ways in which novice teachers conceptualize sustainability and ESD. The insights from this research might serve to inform teaching and learning practices in the undergraduate and postgraduate teaching courses and to prepare teachers more adequately to implement ESD.
Keywords: novice teachers; education for sustainable development (ESD); teachers’ beliefs; knowledge; understanding